Relação entre o nível lexical dos alunos e a coesão referencial em textos argumentativos: uma experiência com o terceiro ano do ensino médio da Escola Lameira Bittencourt - Castanhal/PA - SANTOS, Joelson Gama dos (2020)
This work inserted in the area of Textual Linguistics has as general objective to analyze the cohesive and lexical knowledge of the students of a class of the 3rd year of High School, of a state public school in Castanhal city, in the state of Pará, in Brazil, relating this to the development of cohesion reference. Specifically, it aims to examine the lexical level and the occurrence of referential cohesion mechanisms in argumentative texts. This research has as theoretical foundation Koch (2010), Fávero (2003), Marcuschi (2012), Val (2006), Cançado (1995), Cardoso (1999), among other authors dedicated to the study of linguistics, human language in its various aspects. This research follows the qualitative and quantitative methods, and can be classified as descriptive and explanatory, of an applied nature, being carried out in three stages: 1) Collection of material to compose the research corpus, through the application of two activities: a production textual and an activity of lexical comprehension and production; 2) Bibliographic research; 3) Analysis and interpretation of the corpus and data obtained. The results showed that the lexical “limitation” appears as an adverse factor to the students' performance regarding the use of lexical reiteration referential cohesion mechanisms in dissertative argumentative texts.